Impact of the tiger‐nut milk co‐product on fibre‐enriched bread processing and storage: crumb structure‐moisture‐texture relationships. (28th December 2022) - Verdú, Samuel; Alava, Cecibel; Barat, José M.; Carrascosa, Conrado; Grau, Raúl
Summary: The effect of including tiger‐nut milk co‐product on the bread‐making process was studied. The impact of three wheat flour substitution co‐product levels (5%, 10% and 20%) was tested by comparing to a control (pure wheat) as regards fermentation kinetics and baking phase, as well as their implications on the physicochemical features of breads (crumb internal structure, moisture and texture distribution) just after processing and during storage. The dough fermentation kinetics showed significant differences: reducing maximum height at 60 min and maximum growth rate with an increasing co‐product concentration. However, water retention in baking was the same for them all despite their differences in volume. These facts significantly affected the crumb internal structure, which was successfully characterised by an image analysis technique. Crumb moisture‐structure‐texture relationships were analysed in two different zones of cross‐section bread slices. The results showed how an increasing co‐product level enhanced the homogenization of moisture distribution and hardness across crumb zones, and also reduced the structure differences between them. Moisture and hardness presented high correlation levels with changes in the structure of crumb zones during storage, which allowed the significant effect of co‐product on the crumb moisture‐structure‐texture relationships to be knownin both the bread‐making process and storage time.